2000
DOI: 10.1021/np000347f
|View full text |Cite
|
Sign up to set email alerts
|

Kinmoonosides A−C, Three New Cytotoxic Saponins from the Fruits of Acacia concinna, a Medicinal Plant Collected in Myanmar

Abstract: Three genuine saponins, named kinmoonosides A-C (1-3), have been isolated, together with a new monoterpenoid (4), from a methanolic extract of the fruits of Acacia concinna. The structures of kinmoonosides A-C were elucidated on the basis of spectral analysis as 3-O-¿alpha-L-arabinopyranosyl(1-->6)-[beta-D-glucopyranosyl(1-->2) ]-b eta-D-glucopyranosyl¿-21-O-¿(6R, 2E)-2-hydroxymethyl-6-methyl-6-O-[4-O-(2'E)-6'-hydroxyl-2'-hydroxymet hyl-6'-methyl-2',7'-octadienoyl-beta-D-quinovopyranosyl]-2, 7-octadienoyl¿acac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 23 publications
4
62
0
Order By: Relevance
“…Compounds 1-3 showed significant cytotoxic activity against human HT-1080 fibrosarcoma cels, with ED 50 values of 0.70, 0.91, and 2.83 lM, respectively (Tezuka et al 2000). Their cytotoxicity was greater than that of 5-fluorouracil (ED 50 , 8.0 lM).…”
Section: Kinmoonosidesmentioning
confidence: 97%
See 2 more Smart Citations
“…Compounds 1-3 showed significant cytotoxic activity against human HT-1080 fibrosarcoma cels, with ED 50 values of 0.70, 0.91, and 2.83 lM, respectively (Tezuka et al 2000). Their cytotoxicity was greater than that of 5-fluorouracil (ED 50 , 8.0 lM).…”
Section: Kinmoonosidesmentioning
confidence: 97%
“…The pod has been used as a skin tonic, a shampoo, an expectorant, a purgative and an emetic agent (Khory and Katrak 1999). The MeOH extract of the fruits of A. concinna was shown to exhibit significant cytotoxicity against human HT-1080 fribrosarcoma cells (Tezuka et al 2000). Then, the authors examined the constituents which were responsible of this activity and identified three genuine saponins named kinmoonosides A-C (1-3) (Fig.…”
Section: Kinmoonosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds of the plant are used in Chinese traditional medicines for the treatment of stomach disorders. 1) In the course of our studies on antiproliferative natural products, 2) we found that the 95% EtOH extract of the seeds of A. blepharocalyx showed potent antiproliferative activity against human HT-1080 fibrosarcoma cells 3) (ED 50 , 7.3 mg/ml) and highly liver metastatic murine colon 26-L5 carcinoma cells 4) (ED 50 , 33.2 mg/ml). Thus, the extract was separated into hexane, ether and residual fractions, and the latter two fractions were found to show more potent antiproliferative activity than the former fraction; ED 50 values against HT-1080 fibrosarcoma and colon 26-L5 carcinoma cells: hexane fraction, 7.1 and 62.8 mg/ml; ether fraction, 9.0 and 5.0 mg/ml; residual fraction, 12.3 and 6.8 mg/ml, respectively.…”
mentioning
confidence: 97%
“…5-Fluorouracil used as positive control had an ED 50 value of 8.0 mm. Possibly the ester group at C(21) of the aglycone in these saponins might intensify the cytotoxicity [225].…”
Section: Acacia Concinnamentioning
confidence: 99%